WHAT IS THE IMPACT OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE? CASE STUDY IN BANK JATIM INTERNAL AUDIT DIVISION - Nuzula, Salsabila Firdausi; Irianti, Lingga Resvita; Prastiwi, Dewi (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study aims to describe the effect of reward and punishment on employee performance to understand the impact and effectiveness of the use of these two mechanisms in increasing employee productivity and motivation, and to determine the level of employee motivation at Bank Jatim Internal Audit Division. This type of research is qualitative research by conducting interviews. The findings show that positive motivation in the form of adequate salary, performance-based bonuses, and career advancement opportunities have a greater impact on performance than negative motivation such as punishment, fines, criticism, and reprimands. Respondents stated that fair and clear financial incentives, along with opportunities for career growth and development, provide a strong impetus for employees to improve their productivity and work quality.